Circular economies for lithium-ion batteries and challenges to their implementation - Anil Kumar Vinayak; Matthew Li; Xiaozhou Huang; Pei Dong; Khalil Amine; Jun Lu; Xiaolei Wang (Next Materials)
Global efforts to tackle climate change and the rise in popularity of electric vehicles and portable electronic devices have engendered a demand explosion for lithium-ion batteries (LIBs). Effectuated by the green and digital revolution, this exponential rise in the demand for LIBs raises a host of logistical and environmental concerns centered around raw materials, such as metals lithium and cobalt, indispensable to its production. Exclusive reliance on mining to provide raw materials for LIB production introduces a supply risk and exacerbates the negative implications of mining operations. The long-term solution to avoid bottlenecks in LIB production is the creation of a circular economy by consolidating the LIB value chain with recycling, regeneration and upcycling operations. This paper presents a perspective on circular economies and explores the need to incorporate its principles for a sustainable lithium-powered future. The challenges impeding the development of a fully realized circular economy for LIBs and the ongoing research endeavors to overcome these challenges are also addressed.